Beyond Allergies—Updates on The Role of Mas-Related G-Protein-Coupled Receptor X2 in Chronic Urticaria and Atopic Dermatitis - Liron Lerner; Magda Babina; Torsten Zuberbier; Katarina Stevanovic (Cells, 2024)
Mast cells (MCs) are an important part of the immune system, responding both to pathogens and toxins, but they also play an important role in allergic diseases, where recent data show that non-IgE-mediated activation is also of relevance, especially in chronic urticaria (CU) and atopic dermatitis (AD). Skin MCs express Mas-related G-protein-coupled receptor X2 (MRGPRX2), a key protein in non-IgE-dependent MC degranulation, and its overactivity is one of the triggering factors for the above-mentioned diseases, making MRGPRX2 a potential therapeutic target. Reviewing the latest literature revealed our need to focus on the discovery of MRGPRX2 activators as well as the ongoing vast research towards finding specific MRGPRX2 inhibitors for potential therapeutic approaches. Most of these studies are in their preliminary stages, with one drug currently being investigated in a clinical trial. Future studies and improved model systems are needed to verify whether any of these inhibitors may have the potential to be the next therapeutic treatment for CU, AD, and other pseudo-allergic reactions.